(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Evidence suggests that during caesarean section, single-dose antibiotic prophylaxis has comparable efficacy to multiple-dose antibiotic prophylaxis but with a lower cost and risk of antibiotic resistance. However, most hospitals in Bangladesh, including the study site, are still using antibacterial medications perioperatively and postoperatively for a variable time. This study aimed to compare the effectiveness of single- versus multiple-dose antibiotic prophylaxis to prevent post-caesarean section infections. Materials and methods: This open-label, randomized controlled trial involved 140 consenting patients subjected to a caesarean section at Chattagram International Medical College Hospital (CIMCH). They were distributed randomly into single-dose and multi-dose arms. Subjects in both arms received intravenous cefazolin (1g) after cord clamping; subjects in the multi-dose arm received additional parenteral doses 12 hourly for 24h and then cefixime, 200mg tablets twice daily for six days. The patients were monitored for twoweeks for evidence of wound infection and febrile morbidity. Results: Both the groups were similar regarding their sociodemographic and clinical characteristics. There was no statistical difference in the incidence of febrile morbidity (7.1% versus 2.9%, p=.341) wound discharge (4.3% versus 3.9%, p=1.0) and wound infection (4.3% versus 1.4%, p=.62). The median duration of hospital stay was similar in both groups (3 days). Conclusion: Single-dose cefazolin is as effective as multiple doses for antibiotic prophylaxis to prevent postcaesarean section infections. Adopting this approach would reduce the cost of prophylactic antibiotics, the workload for staff and antibiotic resistance. JCMCTA 2022 ; 33 (2) : 55-59